PENGAWASAN SATUAN POLISI PAMONG PRAJA (SATPOL PP) TERHADAP USAHA COFFEE SHOP DI KOTA PEKANBARU TAHUN 2022 - Pardosi, Ellia Marlina; Tinov, M.Y. Tiyas (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The growth of coffee shop businesses in Pekanbaru City provides good economic opportunities, but this business opportunity makes many coffee shop business actors run their businesses without taking care of business licenses first, potentially harming the surrounding community. The purpose of this research is to find out the supervision and factors that influence the supervision of the Civil Service Police Unit (Satpol PP) of coffee shop businesses in Pekanbaru City in 2022. The theory used is the theory of supervision process from Kadarman. The method in this research uses a qualitative approach with descriptive qualitative research type. The data collection method in this study was carried out by interview and documentation. The results of this study indicate that the Supervision of the Pekanbaru City Pamong Praja Police Unit of the coffee shop business in Pekanbaru City has not been implemented optimally. This can be seen from the data that shows that the number of coffee shops that have licenses is still very small such as in Sail District which only has 3 licensed coffee shops and there are still coffee shops that violate the specified operating hours. The factors that influence the supervision of the Pekanbaru City Pamong Praja Police Unit on the coffee shop business in Pekanbaru City in 2022 are the minimal supervision personnel team, the facilities that are still lacking are provided and the irregular supervision system is an inhibiting factor to the supervision of coffee shop operations. Through this research, it is hoped that in conducting supervision of the coffee shop business in Pekanbaru City, the Pekanbaru City Pamong Praja Police Unit will carry out regular / routine supervision and evaluate things that are deviant and take immediate preventive action so that there are not more coffee shops that violate the rules. Keywords: Supervision, Coffee Shop, License